2001
DOI: 10.1017/s0950268801005817
|View full text |Cite
|
Sign up to set email alerts
|

Day-care and meningococcal disease in young children

Abstract: The Republic of Ireland has the highest incidence of meningococcal disease in Europe with 40% of all cases occurring in children under the age of 5 years. Attending day-care increases the risk of certain infections, including Haemophilus influenzae type b (Hib) meningitis. The risk of meningococcal disease associated with day-care is not known. We conducted a case-control study among pre-school children with 130 laboratory-confirmed cases and 390 controls, matched on age, gender and place of residence, to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The risk assessment should take into account duration and closeness of contact, as the risk of further cases is likely to be higher in settings similar to households, where risk of exposure to respiratory droplets would be more likely. Some studies found a higher risk for IMD in more crowded household settings [51,[83][84][85] and crowded conditions were described in several day-care-associated outbreaks in the USA [13,14]. Thus children in the same group as the index case who have spent long periods in the same room (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The risk assessment should take into account duration and closeness of contact, as the risk of further cases is likely to be higher in settings similar to households, where risk of exposure to respiratory droplets would be more likely. Some studies found a higher risk for IMD in more crowded household settings [51,[83][84][85] and crowded conditions were described in several day-care-associated outbreaks in the USA [13,14]. Thus children in the same group as the index case who have spent long periods in the same room (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to disentangle the independent effects of socioeconomic and demographic variables that are highly correlated. For families with a large number of children and crowded living conditions, an increased risk of invasive meningococcal disease has already been noted elsewhere [28][29][30][31]. The association with socioeconomic status is not surprising, [32,33], but knowing what biological mechanisms are involved is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies have suggested that attendance at childcare centres is not associated with a risk of meningococcal disease and might reduce the risk of IMD by removing young children from close and prolonged contact with adults (carriers). 21,22 Australian guidelines limit chemoprophylaxis in childcare settings to children and staff in the same room group attended by a single index case. 23 This is on the basis of same room ('household') contact for a period of more than 4 h in the 7-day period preceding onset of IMD in the case.…”
Section: Discussionmentioning
confidence: 99%